Efektifitas Pelaksanaan Eksekusi Denda Tilang Di Kabupaten Pulang Pisau - Muhamad Yusuf; Turyan Indah Nurcahyanti (Pencerah Publik, 2018)
This research aims to determine the mechanism of execution of fines of money from the Pulang Pisau Affairs attorney in the case of criminal acts of traffic violations, as well as to find out what matters for the Prosecutor State of the Pulang Pisau in carrying out its duties or roles as an execution of a fine of money in a criminal act of traffic violations, and knowing the actions taken as a solution to the problem. This research uses qualitative research methods. The results of this research can be known the effectiveness of the execution of fine speeding tickets in the state Attorney Pulang Pisau Office has shown positive results, this is demonstrated by the number of cases that have been executed as a percentage of Bigger than the ticketed thing that is still in arrears. However, the arrears that have not been completed can still require follow-up completion, given the magnitude of potential state acceptance that can be obtained from the payment of fine ticketed. The obstacles faced by the State prosecutor's Office in implementing the execution of fine ticketed are among other tickets that are not immediately paid by the violators, because of the ticket violators who are not residents originating from the Pulang Pisau but only riders passing through the Pulang Pisau; Violators reasoned if the busy factor had not attended trial; As well as the amount of workload received by the employees makes the handling of speeding things less efficient.